2022
DOI: 10.1007/s10584-022-03344-9
|View full text |Cite|
|
Sign up to set email alerts
|

The role of human-induced climate change in heavy rainfall events such as the one associated with Typhoon Hagibis

Abstract: Around October 12, 2019, torrential rainfall from Typhoon Hagibis caused large-scale flooding in a large area around the metropole region of Tokyo leading to large-scale destruction including losses of lives, livelihoods, and economic losses of well over $10 bn US dollars. In this paper we use a multi-method probabilistic event attribution framework to assess the role of human-induced climate change in the heavy rainfall event responsible for a large proportion of the damages. Combining different observational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Then, the modelbased estimate and the observations-based estimate are combined to give an overarching attribution statement (synthesis). The synthesis is calculated using two approaches described below, with further detail and equations available in Li and Otto (2022). In this particular study, the final uncertainty reported in the overarching attribution statement combines these two approaches.…”
Section: Multi-model Attributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the modelbased estimate and the observations-based estimate are combined to give an overarching attribution statement (synthesis). The synthesis is calculated using two approaches described below, with further detail and equations available in Li and Otto (2022). In this particular study, the final uncertainty reported in the overarching attribution statement combines these two approaches.…”
Section: Multi-model Attributionmentioning
confidence: 99%
“…First, ignoring model uncertainties beyond the model spread (i.e. ignoring model biases that are shared between the models used and, therefore, cannot be detected by differences between them, see also Li and Otto 2022), the weighted average of the combined model-based estimate (dark red bar) and the observations-based estimate (blue bar) is calculated and shown as magenta bars in Fig. 8.…”
Section: Multi-model Attributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Economic damage from flooding associated with Hurricane Harvey (Frame et al, 2020a;Frame et al, 2020c) 4. Economic damage from flooding associated with Typhoon Hagibis (Li and Otto, 2022) Recently Perkins-Kirkpatrick et al, (2022) has drawn attention to the drawbacks of the Attributable Costs method. They point out that it cannot be assumed that a FAR for an extreme weather or climate event is linearly related to the impact of that event.…”
Section: Attributable Costsmentioning
confidence: 99%
“…Being located in the western North Pacific basin, Japan is also susceptible to frequent landfall of extratropical cyclones, which bring heavy rain and strong wind. A recent typhoon in Japan, Typhoon Hagibis, hit the eastern part of the country in October 2019 and caused an economic loss of over USD10 billion dollars (Li & Otto, 2022).…”
Section: Introductionmentioning
confidence: 99%